2001
DOI: 10.1080/00958970108022642
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Complexes of Silver Halides and Tetramethylthiuram Monosulfides

Abstract: The preparation and characterization of 1 : 1 adducts of silver halides AgX (X = C1, Br, I) with N,N,N',N'-tetramethylthiuram monosulfides is reported. The products are characterized by elemental analyses, magnetic measurements and IR-Raman spectroscopy. The data are interpreted in terms of a halogen-dibridged structure of DZh symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the control experiments without any catalyst (entry 14) showed that catalyst was not crucial in this reaction. To our delight, the reaction would be significantly promoted when a series of bases were added (entries [15][16][17][18][19][20][21][22][23], and the screening of bases showed that Na 2 CO 3 was the best. Thus, the optimal reaction conditions were summarized in entry 15, Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the control experiments without any catalyst (entry 14) showed that catalyst was not crucial in this reaction. To our delight, the reaction would be significantly promoted when a series of bases were added (entries [15][16][17][18][19][20][21][22][23], and the screening of bases showed that Na 2 CO 3 was the best. Thus, the optimal reaction conditions were summarized in entry 15, Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[22] However, there are very few reports on thiuram monosulfides. [23] Uchida [24] reported that thiuram monosulfide could inhibit peptidyl-prolyl cis/trans isomerase activity in HeLa cells. Our group recently reported the thiocarbamates protected indoles by using TMTM.…”
Section: Introductionmentioning
confidence: 99%